1998
DOI: 10.1109/16.725254
|View full text |Cite
|
Sign up to set email alerts
|

Negative capacitance effect in semiconductor devices

Abstract: Nontrivial capacitance behavior, including a negative capacitance (NC) effect, observed in a variety of semiconductor devices, is discussed emphasizing the physical mechanism and the theoretical interpretation of experimental data. The correct interpretation of NC can be based on the analysis of the time-domain transient current in response to a small voltage step or impulse, involving a self-consistent treatment of all relevant physical effects (carrier transport, injection, recharging etc.). NC appears in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(172 citation statements)
references
References 46 publications
7
163
2
Order By: Relevance
“…26 Hence the magnitude of ⌬C is enhanced as well and the total capacitance C geo + ⌬C may become negative. The relevant time scales can be best understood in the carrier transient response to a step potential: 14 For a short time period after the voltage step, such that even the fastest carriers cannot respond, only the displacement current contributes to the ͑geometrical͒ capacitance, which is determined by the dielectric permittivity. Subsequently, as both injection contacts are set Ohmic, the fastest carriers ͑holes͒ will determine the transient field in the following time interval.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…26 Hence the magnitude of ⌬C is enhanced as well and the total capacitance C geo + ⌬C may become negative. The relevant time scales can be best understood in the carrier transient response to a step potential: 14 For a short time period after the voltage step, such that even the fastest carriers cannot respond, only the displacement current contributes to the ͑geometrical͒ capacitance, which is determined by the dielectric permittivity. Subsequently, as both injection contacts are set Ohmic, the fastest carriers ͑holes͒ will determine the transient field in the following time interval.…”
Section: Theorymentioning
confidence: 99%
“…Recently, negative capacitances have been reported on a variety of devices that were based on organic materials [1][2][3][4] or on crystalline or amorphous inorganic semiconductors. [5][6][7][8][9][10][11][12][13][14] Equally numerous explanations for this negative capacitance ͑NC͒ have been presented that involved minority carrier flow, 1,[3][4][5] interface states, 9,13 slow transient time of injected carriers, 14 charge trapping, 2,3,[10][11][12] or space charge. 6 The bulk of these descriptions are either based on phenomenological arguments or based on device representation in an equivalent circuit.…”
Section: Introductionmentioning
confidence: 99%
“…current lags behind voltage) and the reactive component of the conduction current is larger than the displacement current. Ershov et al have discussed the NC effect with emphasise on theoretical interpretation of this phenomenon [27]. They have obtained general rela− tionships between the transient current in the time−domain and capacitance in the frequency domain and have shown that those relationships follow from the Fourier transform, and are independent of particular physical processes and ap− plicable to all types of electronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the existence of an insulator layer, native or deposited at metalsemiconductor (MS) interface, changes the C-V and G/ω characteristics of the diode. Negative capacitance (NC) and anomalous peak have been observed in the forward bias C-V characteristics of MS or MIS SBDs [10][11][12][13][14][15][16][17][18]. The NC has been attributed to the interface states, the contact injection and minority carrier injection effects * corresponding author; e-mail: farukozdemir@sdu.edu.tr and the anomalous peak can occur due to interface states (N ss ) and R s [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally the C-V and G/ω-V characteristics of Schottky barrier diodes (SBDs) are frequency independent, particularly at high frequency, and show an increase with the increasing forward bias voltage [8][9][10][11][12][13][14]. Deviations from this case can be seen at low and moderate frequencies, in depletion and accumulation regions, due to the contribution of carriers at interface states, interfacial insulator layer and R s of device.…”
Section: Introductionmentioning
confidence: 99%